Antimicrobial photodynamic therapy against metronidazole-resistant dental plaque bactéria - Zago, Lucas Henrique de Paula [UNESP]; de Annunzio, Sarah Raquel [UNESP]; de Oliveira, Kleber Thiago; Barbugli, Paula Aboud [UNESP]; Valdes, Belen Retamal; Feres, Magda; Fontana, Carla Raquel [UNESP] (Elsevier, 2020)
The antimicrobial photodynamic therapy (aPDT) has stood out as an alternative and promising method of disinfection and has been exploited for the treatment of oral bacteria. In this study, we evaluate in vitro the action of aPDT, mediated by methylene blue, chlorin-e6, and curcumin against clinical subgingival plaques that were resistant to metronidazole. The sensitivity profile of the samples to metronidazole was analyzed by the agar dilution method. Cell viability in the planktonic and biofilm phase was assessed by CFU / mL. The composition of the biofilm was evaluated by the checkboard DNA-DNA Hibrydization technique. Photosensitizers internalization was qualitatively assessed by confocal fluorescence microscopy (CLSM). The aPDT mediated by the three photosensitizers tested was able to reduce the totality of the planktonic microbial load and partially reduce the biofilm samples. The analysis performed by CLSM showed that the photosensitizers used in the application of aPDT were able to permeate the interior of the biofilm. The aPDT has been shown to be useful in a supportive and effective approach to the treatment of periodontal disease.
Keywords: Antimicrobial photodynamic therapy; Chlorin-e6; Curcumin; Methylene blue; Periodontal disease; Resistant sample